2011
DOI: 10.15381/rivep.v22i3.256
|View full text |Cite
|
Sign up to set email alerts
|

EVALUACIÓN DE DOS MÉTODOS DE CRIOPRESERVACIÓN DE EMBRIONES DE LLAMAS SOBRE LAS TASAS DE SUPERVIVENCIA in vivo e in vitro.

Abstract: RESUMENEl objetivo del estudio fue evaluar el efecto de dos métodos de criopreservación sobre la supervivencia in vivo e in vitro de embriones de llama. Se recuperaron 73 embriones en estadio de blastocisto eclosionado mediante una técnica no quirúrgica a los 6.5 días post servicio en llamas superestimuladas. Las llamas receptoras se distribuyeron aleatoriamente en grupo Control (n = 14), de vitrificación (n=30) y de congelación lenta (n=29). Para la vitrificación, los embriones fueron expuestos a la solución … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…They attributed the low results to the implementation of a single natural mating for each superstimulated female. Other studies have used the same ovarian superstimulation treatment, two days after administering GnRH in the presence of a dominant follicle, registering in the case of Vásquez (24), a mean of 6.5 ± 3.1 CLs/female and recovering 4 ± 2.6 embryos/female, while Aller et al (22) observed 5.5 ± 3.1 CLs/female and obtained 2.1 ± 2.2 embryos/female. The embryo recovery rate achieved by Vásquez (24) was similar to that obtained in our study (65.3 vs. 66.7% respectively), both of which were superior to the rate of 40.7% obtained by Aller et al (22).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…They attributed the low results to the implementation of a single natural mating for each superstimulated female. Other studies have used the same ovarian superstimulation treatment, two days after administering GnRH in the presence of a dominant follicle, registering in the case of Vásquez (24), a mean of 6.5 ± 3.1 CLs/female and recovering 4 ± 2.6 embryos/female, while Aller et al (22) observed 5.5 ± 3.1 CLs/female and obtained 2.1 ± 2.2 embryos/female. The embryo recovery rate achieved by Vásquez (24) was similar to that obtained in our study (65.3 vs. 66.7% respectively), both of which were superior to the rate of 40.7% obtained by Aller et al (22).…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have used the same ovarian superstimulation treatment, two days after administering GnRH in the presence of a dominant follicle, registering in the case of Vásquez (24), a mean of 6.5 ± 3.1 CLs/female and recovering 4 ± 2.6 embryos/female, while Aller et al (22) observed 5.5 ± 3.1 CLs/female and obtained 2.1 ± 2.2 embryos/female. The embryo recovery rate achieved by Vásquez (24) was similar to that obtained in our study (65.3 vs. 66.7% respectively), both of which were superior to the rate of 40.7% obtained by Aller et al (22). Based on inducing ovulation with LH, Huanca et al (26) registered a higher mean of CLs (10.1 ± 2.9 CLs/animal) at the time of embryo recovery after administering eCG two days after LH.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sin embargo, para llevar a cabo reproducción animal asistida mediante técnicas de transferencia nuclear o para la creación de bibliotecas genómicas, es necesario entender y aplicar adecuadamente las técnicas de conservación de material biológico (Ávila-Portillo et al 2006;León-Quinto et al 2011). Una de estas técnicas es la criopreservación en la cual se almacenan células germinales, somáticas o tejidos, en crioprotectores a bajas temperaturas, permitiendo que a la descongelación, se logren restablecer sus condiciones fisiológicas normales con una considerable tasa de viabilidad (Vásquez et al 2011).…”
Section: Introductionunclassified